Fortaleza na ponta do anzol - Monteiro Júnior, Francisco Hélio (2008)
The present study analyzes the oppositions, as well the dialogues, between urban spaces and natural environment on the constitution of Fortaleza City (capital of the Ceará State - Brazil)as a "regional mepropolis". With the focus on the lake-dwelling fishermen, this work points to the close relationship among urban development and the fishing activities that occur by the border of this process. It also underlines the conflict in the discourses relative to the diverging interests of the fishermen crafts, entrepeneurs and the public authorities about the uses and appropriations of the pounds. The empirical research was made at the Parangaba Lagoon and describes the sociabilities invented in a place "liminar" condition - relationships of the genders, the corporal movements and the practices of fishing in fresh water.